KAPASITAS PEMERINTAH DESA TANAH MERAH KECAMATAN TANAH MERAH KABUPATEN INDRAGIRI HILIR DALAM PENGELOLAAN DANA DESA TAHUN 2021 - Kusuma, Aditya Wafiq Dwi; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Basically, the Village Government is the executor of policy, especially in terms of managing Village Funds. The capacity of the village government in managing village funds is so important so that village programs can run according to plan. So, the Tanah Merah Village Government is required to have adequate capacity so that the management of village funds in 2021 can run well and in accordance with the regulations. The purpose of this research is to determine the capacity of the Tanah Merah Village Government, Tanah Merah District, Indragiri Hilir Regency in Managing Tanah Merah Village Funds in 2021. In achieving the objectives of this research, the author uses Soeprapto's capacity theory, namely system level, organizational level and individual level. The research approach used is a qualitative approach. The type of research used is descriptive. The location of this research is in Tanah Merah Village, Tanah Merah District, Indragiri Hilir Regency, precisely at the Tanah Merah Village Government Office and several stakeholders who have authority in this research. The types and sources of research data are divided into primary and secondary data with data collection techniques through interviews and secondary data in the form of supporting data related to village fund management capacity. The results of this research are that the capacity of the Tanah Merah Village Government in managing village funds is still not optimal. Lack of individual capacity has a significant impact on the village fund management process. So, there are administrative problems, namely late disbursement and discrepancies in the percentage of village funds which cause the use of village funds to not be optimal and village programs not running as they should. The Village Government has made efforts to increase capacity, however, inadequate individual capacity hampers the capacity building process. Keywords: Capacity at system level, capacity at organizational level, capacity at individual level.